Factors Influencing Thai Youth Tourists’ Intention to Visit Lanna Cultural Heritage Sites - Onpium, Pintusorn; Kaewnuch, Kanokkarn (Siam University Journal of Business Administration, 2022)
Due to lack of the readiness of potential and good management in Lanna cultural heritage tourism resources, this weakness affected a number of Thai youth tourists visiting Lanna cultural heritage sites causing the number to decrease. The purpose of this study was to identify and perceive factors associated with the value of Lanna cultural heritage tourism resources and motivation factors influencing Thai youth tourists’ intention to visit Lanna cultural heritage sites in order to have a guideline in management of Lanna cultural heritage tourism resources that led to attract more Thai youth tourists. This study was designed to examine the value of Lanna cultural heritage tourism resources and motivation factors influencing Thai youth tourists’ intention to visit Lanna cultural heritage sites. Four indicators of the value of cultural heritage measure were confirmed and combined with four indicators of motivation factors to predict Thai youth tourists’ intention to visit. The results revealed that both of the four indicators of the value of cultural heritage and the four indicators of motivation factors influenced Thai youth tourists’ intention to visit Lanna cultural heritage sites.